Very early and late form-to-meaning computations during visual word recognition as revealed by electrophysiology. (December 2022) - Sulpizio, Simone; Arcara, Giorgio; Lago, Sara; Marelli, Marco; Amenta, Simona
Abstract: We used a large-scale data-driven approach to investigate the role of word form in accessing semantics. By using distributional semantic methods and taking advantage of an ERP lexical decision mega-study, we investigated the exact time dynamic of semantic access from printed words as driven by orthography-semantics consistency (OSC) and phonology-semantics consistency (PSC). Generalized Additive Models revealed very early and late OSC-by-PSC interactions, visible at 100 and 400 msec, respectively. This pattern suggests that, during visual word recognition: a) meaning is accessed by means of two distinct and interactive paths – the orthography-to-meaning and the orthography-to-phonology-to-meaning path –, which mutually contribute to recognition since early stages; b) the system may exploit a dual mechanism for semantic access, with early and late effects associated to a fast-coarse and a slow-fine grained semantic analysis, respectively. The results also highlight the high sensitivity of the visual word recognition system to arbitrary form-meaning relations.